Students’ Psychology: An Analysis of Individual Characteristics in The Learning Context - Adawiyah, Madinah; Hamid, Asep Lukman; Hafifah, Nadiyatur Rohmah; Al Adawiyah, Robiah (Addabani: Interdisciplinary Journal of Islamic Education, 2026)
A thorough understanding of individual learner characteristics is crucial in contemporary education, given their impact on learning effectiveness. The increasingly complex diversity of learners, driven by socio-cultural and technological factors, demands a comprehensive identification and analysis of the factors shaping individual characteristics and their implications for teaching practices. Research gaps in integrating empirical findings for holistic intervention models remain apparent. This study aims to analyze the determinants of individual learner characteristics, drawing on the genetic-environmental interactionism framework and the theory of multiple intelligences, and evaluate their implications for the development of differentiated teaching strategies to optimize learning outcomes. This study employed a comprehensive literature review design, drawing on primary and secondary sources from leading academic databases. Data were analyzed thematically using qualitative content analysis to identify patterns and relationships between variables. Key findings indicate that individual characteristics are dynamic products of genetic and environmental interactions, contributing significantly to learning styles and intelligence profiles. This diversity is positively correlated with the need for differentiated teaching approaches, which require adaptation of materials, methods, and evaluation. The integration of adaptive learning technologies has also been identified as enhancing the engagement and achievement of diverse learners. Individual characteristics are multifaceted constructs that require serious attention in pedagogy. It is recommended to develop an evidence-based framework for curriculum planning that is responsive to individual diversity, and to enhance teacher professionalism in learning differentiation strategies and the use of adaptive technology.